Alginate oligosaccharides increase boar semen quality by affecting gut microbiota and metabolites in blood and sperm - Han, Hui; Zhou, Yexun; Xiong, Bohui; Zhong, Ruqing; Jiang, Yue; Sun, Haiqing; Tan, Jiajian; Zhang, Bin; Guan, Chang; Schroyen, Martine; Chen, Liang; Zhao, Yong; et al. (Frontiers in Microbiology, 2022)
Alginate oligosaccharides (AOS), natural polymers from brown seaweeds (such as Laminaria japonica, Undaria pinnatifida, Sargassum fusiforme), have been reported to possess many beneficial advantages for health. In current study, after nine weeks dietary supplementation, AOS 10 mg/kg group (AOS 10) group increased boar sperm motility. Semen volume per day, sperm concentration and in vitro fertilization rate exhibited an increasing trend in AOS10 over control group (CON). Moreover, AOS10 increased the levels of the beneficial microbiota Bifidobacterium, Coprococcus, Butyricicoccus to benefit blood and sperm metabolites, and important sperm proteins such as gelsolin, Zn-alpha2 glycoprotein, Cation Channel Sperm-Associated Protein, outer dense fiber of sperm tails, etc. It was interesting that sperm metabolites, blood metabolites, and fecal microbiota were well correlated together or with sperm motility or concentration, and AOS had a long-term beneficial advantage on boar semen quality. AOS may be used as dietary additives for improving semen quality.